Moral dilemmas of the development of postmodern societies - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2019)
The aim of the article is to present tensions that occur in social, cultural, political, and technological spheres as a result of the development of postmodern societies. The changes that have been taking place in those areas involve, along with unquestionable benefits, a type of risk which, without any moral reflection, can cause a serious global crisis. The postmodern times should be understood as a continuation of the modern formation where all typical features of modernism take a more radical form. The postmodern specific style of life is characterised by uncertainty, the unpredictability of the future, as well as a decline of traditional values and morals. Moreover, the present postmodern tendencies in the area of morals can hinder the right course of development of society, economy and ecology.